Myocardial remodelling and recovery in dilated cardiomyopathy - Tayal, Upasana (JRSM Cardiovasc Dis, 2017)
Myocardial reverse remodeling has been reported to occur in 25–70% of patients with dilated cardiomyopathy. It is not yet fully understood whether remodeling represents disease remission or cure and which hearts retain this capacity to recover. In this review article we discuss the capacity for recovery in DCM, the prognostic implications of this recovery and potential clinical and imaging predictors for myocardial remodeling.